2017
DOI: 10.1161/circgenetics.116.001738
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Genetic Causes of Sudden Unexpected Death in Children Through Targeted Next-Generation Sequencing Analysis

Abstract: We have identified variants that may assist in the diagnosis of at least 6.3% of autopsy-negative child SUD cases and reduce risk of future SUD in surviving relatives. We recommend a cautious approach to variant interpretation. We also suggest inclusion of cardiomyopathy genes as well as other candidate SUD genes in molecular autopsy analyses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 43 publications
0
22
0
Order By: Relevance
“…A total of 20 original research studies [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] and seven case reports [31][32][33][34][35][36][37] thus met the inclusion criteria for the review, which included at least one infant greater than 1-year-old in their study (►Table 1). One of the seven case reports, however, 34 was also represented in one original research article.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 20 original research studies [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] and seven case reports [31][32][33][34][35][36][37] thus met the inclusion criteria for the review, which included at least one infant greater than 1-year-old in their study (►Table 1). One of the seven case reports, however, 34 was also represented in one original research article.…”
Section: Resultsmentioning
confidence: 99%
“…the results of a molecular diagnosis have clinical value for relatives who may carry the same mutations; some of which are already clinically actionable. 6,12 This review has collated the results from previous molecular autopsy related studies and showed that a median of 4% of previous SIDS cases can potentially be resolved by a molecular autopsy. While this was significantly lower than the yield from older cohorts of SUDY, these results would have been of particular value to the respective family members.…”
Section: Discussionmentioning
confidence: 99%
“…The availability of large panels and of exome screening has allowed investigators to discover pathogenic variants in genes initially unexpected to be related to the phenotype. In the case of Pkp2 , variants have been detected in idiopathic ventricular fibrillation and SCD (36, 37), possible catecholaminergic polymorphic ventricular tachycardia (38), HCM, DCM and left ventricular non-compaction (3941). The association between Pkp2 mutations and idiopathic SCD is not that surprising, considering that often SCD is the earliest manifestation in ACM athletes before the onset of overt cardiomyopathy.…”
Section: Additional Cardiac Phenotypes Linked To Pkp2mentioning
confidence: 99%
“…With the power of massively parallel sequencing, testing a large number of cardiac disease‐associated genes simultaneously has become feasible. There are now several reports of postmortem testing to identify pathogenic variants directly linked to an underlying heritable cardiac disease; hence, the potential for fatal arrhythmia and sudden death . When there is insufficient evidence to classify variants as either benign or pathogenic, they are considered variants of uncertain significance (VUS).…”
Section: Introductionmentioning
confidence: 99%
“…There are now several reports of postmortem testing to identify pathogenic variants directly linked to an underlying heritable cardiac disease; hence, the potential for fatal arrhythmia and sudden death. [1][2][3][4][5][6] When there is insufficient evidence to classify variants as either benign or pathogenic, they are considered variants of uncertain significance (VUS). In our previous study in which 89 cardiac genes were analyzed in a large cohort of 296 sudden unexpected deaths (SUD), 2 we identified a large preponderance of VUS in various genes, including the pacemaker gene, HCN4.…”
Section: Introductionmentioning
confidence: 99%